1989
DOI: 10.1073/pnas.86.8.2592
|View full text |Cite
|
Sign up to set email alerts
|

Native and mutant 5-lipoxygenase expression in a baculovirus/insect cell system.

Abstract: Human 5-lipoxygenase (EC 1.13.11.34), the key enzyme involved in the transformation of arachidonic acid to the potent biologically active leukotrienes, has been overexpressed in insect cells using a baculovirus expression system. A recombinant baculovirus (3B6) carrying the human 5-lipoxygenase coding sequence downstream of the strong polyhedrin protein promoter was isolated. Approximately 48 hr after infection of Spodoptera frugiperda cells with the recombinant baculovirus, maximal intracellular enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
2

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 29 publications
4
25
2
Order By: Relevance
“…Reverse-phase (RP) HPLC analysis was performed as previously described [15]. Briefly, purified 6His-12LX (1 -3 pg) in 100 p1 50 mM sodium phosphate pH 8.0 was incubated with 100 pM arachidonic acid at 37°C for 10 min.…”
Section: Assays Of Purified 1zlipoxygenase Activitymentioning
confidence: 99%
“…Reverse-phase (RP) HPLC analysis was performed as previously described [15]. Briefly, purified 6His-12LX (1 -3 pg) in 100 p1 50 mM sodium phosphate pH 8.0 was incubated with 100 pM arachidonic acid at 37°C for 10 min.…”
Section: Assays Of Purified 1zlipoxygenase Activitymentioning
confidence: 99%
“…In vitro, both 5-LO and 15-LOa undergo a burst phase of activity before reaching a steady rate of product formation and then undergoing suicide inactivation by their respective enzyme products [9,14]. Investigations into the subcellular localization of both 5-LO and 15-LOa have demonstrated that these proteins become membrane associated in a calcium-dependent manner and upon membrane localization their specific activity is increased [16,17].…”
mentioning
confidence: 99%
“…For example, 12-HETE and 15-HETE have been implicated in tumour metastases and the formation of atherosclerotic plaques, respectively [11,12]. The important biological roles of these LO metabolites and the complexity of substrate utilization by members of the LO family emphasize the importance of understanding factors which affect the activity and regulation of these enzymes.Overexpression and characterization of recombinant 5-LO, 12-LO and 15-LOa have been carried out allowing kinetic analysis of these enzymes [9,13,14] and the hypotheses as to the mechanism by which LOs oxygenate fatty acids have been developed [15]. In vitro, both 5-LO and 15-LOa undergo a burst phase of activity before reaching a steady rate of product formation and then undergoing suicide inactivation by their respective enzyme products [9,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five of these histidine residues have been suggested by Shibata et al [19] to be putative iron-binding sites. Funk et al [27], however, reported that site-directed mutation of His362 and His372 within the putative iron-binding domain of human 5-lipoxygenase did not alter the enzyme activity, suggesting that the two residues are not involved in iron binding. Thus, the function of these conserved residues still remains unclear.…”
Section: Discussionmentioning
confidence: 99%